Due Professional Care and Audit Quality: Assessing the Influence of Time Budget Pressure, Accountability, and Auditor Experience - Arista Fauzi Kartika Sari; Dewi Diah Fakhriyyah (Fakultas Ekonomi dan Bisnis, Universitas Udayana bekerjasama dengan Ikatan Sarjana Ekonomi Cabang Bali, 2024)
External auditors, or public accountants, are crucial in fostering trust in corporate financial statements, facilitating stakeholders' informed decision-making by assessing the fairness of these reports. This study focuses on how due professional care, time budget pressure, accountability, and auditor work experience affect audit service quality. Conducted among auditors from Public Accountant Firms in Malang registered with Indonesia's Financial Services Authority (OJK), it uses convenience sampling based on the Slovin formula and employs multiple linear regression for analysis. The results indicate that due professional care, accountability, and auditor work experience significantly contribute to improving audit quality, while time budget pressure shows no substantial effect. This highlights the essential role of due professional care, accountability, and experience in enhancing the quality of audit services provided by public accounting firms, suggesting these factors should be prioritized to maintain high standards in audit practices.